Glucose counteracts isoprenaline effects on ion channel functions in human-induced pluripotent stem cell-derived cardiomyocytes - Qiao, Lin; Fan, Xuehui; Yang, Zhen; El-Battrawy, Ibrahim; Zhou, Xiao-Bo; Akın, Ibrahim (Journal of cardiovascular development and disease, 2022)
Recent studies indicate that the disorder of glucose metabolism in myocardial tissue is involved in the development of Takotsubo syndrome (TTS). This study investigated the effects of a high level of glucose on the pathogenesis of TTS, focusing on the electrophysiological mechanisms. Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) were treated with toxic concentration of isoprenaline (Iso, 1 mM) and a high level of glucose (22 mM) to mimic the setting of TTS and diabetes mellitus (DM). Iso prolonged action potential duration (APD) through enhancing the late sodium channel current and suppressing the transient outward potassium current (Ito). However, a high level of glucose prevented the APD prolongation and the change in Ito. High-level glucose reduced the expression levels of PI3K/Akt, β1-adrenoceptors, Gs-protein, and PKA, suggesting their involvement in the protective effects of high-level glucose against toxic effects of catecholamine. High glucose level did not influence Iso-induced ROS-generation, suggesting that the protective effects of high-level glucose against Iso did not result from changes in ROS generation. High-level glucose may protect cardiomyocytes from the toxic effects of catecholamine excess through suppressing β1-adrenoceptor-Gs-PKA signaling. DM may reduce the risk for occurrence of arrhythmias due to QT prolongation in TTS patients.
Gesehen am 30.04.2024